Grazing Incidence Small-Angle Neutron Scattering: Background Determination and Optimization for Soft Matter Samples - Tetyana Kyrey; Marina Ganeva; Judith Witte; Artem Feoktystov; Stefan Wellert; Olaf Holderer (Applied Sciences, 2021)
Grazing incidence small-angle neutron scattering (GISANS) provides access to interfacial properties, e.g., in soft matter on polymers adsorbed at a solid substrate. Simulations in the frame of the distorted wave Born approximation using the BornAgain software allow to understand and quantify the scattering pattern above and below the sample horizon, in reflection and transmission, respectively. The small-angle scattering from the interfacial layer, visible around the transmitted beam, which might contribute also on the side of the reflected beam, can be understood in this way and be included into the analysis. Background reduction by optimized sample cell design is supported by simulations, paving the way for an optimized GISANS cell.